PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PENGURANGAN MELALUI MEDIA PATAMA PORTABEL DI KELAS I SD - Suli Indriya; Nur Atikoh (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
Basic competence of grade I SD students is expected to be able to reduce whole numbers up to 99. However, in reality there are 67% of grade 1 students in SD who still have difficulty working on pre-cycle question subtraction material. This reflection produced alternative problem solving using portable PATAMA media. Improving learning the researchers carried out cycle I and cycle II. Subjects this study were grade 1 students of SD Modern El Mumtaz, Tuban Regency with a total 9 students. Data acquisition techniques through planning, observation, implementation and reflection. Then analyze the data through quantitative and qualitative techniques. Cycle I, data on student learning outcomes was obtained, namely there were 6 students whose scores were higher than KKM 68 with an average score 78.33. And there were 3 students whose scores below the KKM with an average score 60. Cycle II there was an increase in student learning outcomes, where 8 students had scores higher than KKM, with an average score 92.5. And 1 student whose score is below KKM with an average score 60. Results this study it can be concluded that using portable PATAMA media can improve the learning outcomes of 1st grade elementary school students. Keywords: Learning Outcomes, Portable PATAMA, Subtraction.